2021
DOI: 10.3390/horticulturae7090313
|View full text |Cite
|
Sign up to set email alerts
|

Biostimulatory Action of Vegetal Protein Hydrolysate and the Configuration of Fruit Physicochemical Characteristics in Grafted Watermelon

Abstract: Foliar application of a vegetal-derived protein hydrolysate as a biostimulant was assessed for possible interaction with the ripening of diploid watermelon grafted onto interspecific hybrid rootstock. Assessment encompassed crop performance; fruit morphometric and sensory quality traits; soluble carbohydrates; macrominerals; and bioactive composition at 10, 20, 30, 40, and 50 days post anthesis (dpa). The biostimulant effect on yield components was confounded by the vigorous rootstock effect. Pulp firmness dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
1
5
1
Order By: Relevance
“…Interestingly, the highest total sugar content was detected in the W6 treatment, due to a balanced content of individual free sugars. In contrast to our study, Soteriou et al [42] did not record a significant effect of protein hydrolysates application on the free sugar content of watermelon fruit, whereas a biostimulant that included polysaccharides, vitamins, amino acids, potassium oxide and polypeptides increased glucose and fructose content in pepper fruit (Capsicum annuum L. cv Palermo) [76]. A similar effect was recorded for the application of free amino acids, which increased monosaccharides content in tomato fruit [77], whereas Peris-Felipo et al [58] suggested that only fructose content was affected by silicon application on strawberry plants.…”
Section: Free Sugarscontrasting
confidence: 99%
See 3 more Smart Citations
“…Interestingly, the highest total sugar content was detected in the W6 treatment, due to a balanced content of individual free sugars. In contrast to our study, Soteriou et al [42] did not record a significant effect of protein hydrolysates application on the free sugar content of watermelon fruit, whereas a biostimulant that included polysaccharides, vitamins, amino acids, potassium oxide and polypeptides increased glucose and fructose content in pepper fruit (Capsicum annuum L. cv Palermo) [76]. A similar effect was recorded for the application of free amino acids, which increased monosaccharides content in tomato fruit [77], whereas Peris-Felipo et al [58] suggested that only fructose content was affected by silicon application on strawberry plants.…”
Section: Free Sugarscontrasting
confidence: 99%
“…Interestingly, no significant effect on fruit firmness was recorded for the tested biostimulants in our study, since, according to the literature, Si application is expected to increase fruit firmness due to its involvement in cell wall structure and the induced biosynthesis of lignin and hemicellulose [69,70]. However, our results are in agreement with the study of Soteriou et al [42], who also did not record any significant effect of biostimulant application on the firmness of watermelon fruit flesh, which highlights the impacts the application dose and biostimulant composition may have on fruit quality parameters. The effect of biostimulant formulation application on the proximal composition of watermelon fruit is presented in Table 6.…”
Section: Fruit Quality Parameterssupporting
confidence: 90%
See 2 more Smart Citations
“…To overcome such limitations when seeking the production of high-quality seedlings, the use of substances with biostimulant properties is an interesting technology in sustainable agriculture to face problems related to fertilizer use in agricultural crops (Nardi et al, 2021). Humic substances (HS) have been used to supply nutrients and/ or stimulate the production of phytohormones that lead to root growth that the plant would otherwise not achieve (El-Hai et al, 2019;Qin & Leskovar, 2020a;Soteriou et al, 2021). Previous studies have demonstrated the effect of humic substances as seedling growth modulators, among other beneficial effects (Gomes Júnior et al, 2019;Qin & Leskovar, 2020a;Silva et al, 2022;Targino et al, 2023).…”
Section: Introductionmentioning
confidence: 99%